2018
DOI: 10.1186/s40249-017-0385-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and habitat characterization of mosquito species during the dry season along the Mara River and its tributaries, in Kenya and Tanzania

Abstract: BackgroundVector-borne diseases are increasingly becoming a major health problem among communities living along the major rivers of Africa. Although larger water bodies such as lakes and dams have been extensively researched, rivers and their tributaries have largely been ignored. This study sought to establish the spatial distribution of mosquito species during the dry season and further characterize their habitats along the Mara River and its tributaries.MethodsIn this cross-sectional survey, mosquito larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 49 publications
(61 reference statements)
4
52
0
1
Order By: Relevance
“…5 However, our finding that pfPR was similar in the areas abutting the lake than those that were more inland (39.3% versus 40.9%) suggests that breeding sites located closer to people's homes, such as slow-flowing streams, rain ponds, and vegetation, play an important small-area role in maintaining high malaria transmission patterns in both lakeshore and inland areas. 46 This reasoning is consistent with the observation that most mosquito vectors tend to breed near sites of human habitation 47 and that most fly relatively short distances (< 3 km) to find blood meals, 48 which is considerably shorter than the average distance across districts used to define lakeshore versus more inland areas. Our finding of high GMPD (∼1,000 parasites/μL) among asymptomatic children in the lake-endemic area may have public health relevance if we consider that GMPD > 1,000 parasites/μL may be a surrogate of carrying gametocytes.…”
Section: Discussionsupporting
confidence: 78%
“…5 However, our finding that pfPR was similar in the areas abutting the lake than those that were more inland (39.3% versus 40.9%) suggests that breeding sites located closer to people's homes, such as slow-flowing streams, rain ponds, and vegetation, play an important small-area role in maintaining high malaria transmission patterns in both lakeshore and inland areas. 46 This reasoning is consistent with the observation that most mosquito vectors tend to breed near sites of human habitation 47 and that most fly relatively short distances (< 3 km) to find blood meals, 48 which is considerably shorter than the average distance across districts used to define lakeshore versus more inland areas. Our finding of high GMPD (∼1,000 parasites/μL) among asymptomatic children in the lake-endemic area may have public health relevance if we consider that GMPD > 1,000 parasites/μL may be a surrogate of carrying gametocytes.…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that the same aquatic habitats targeted for Anopheles larval control programmes could also be targeted for culicine larvae control programmes. Previous studies have shown that Anopheles and culicine larvae are likely to occur in the same habitats [43]. Likewise, Anopheles early and late instars were highly correlated at the three sites.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have established that bacteria in the breeding habitat constitute the main food source for larvae enhancing larval growth and the productivity and survival of the adult mosquitoes [8,9,17]. Studies have also demonstrated that higher dissolved oxygen favours the development of Anopheles mosquitoes [37,38].…”
Section: Discussionmentioning
confidence: 99%